Biosynthetic polyphosphate enhances osteogenesis of human periodontal ligament stem cells and promotes periodontal bone regeneration in a murine periodontal bone defect model - Chen, Jiaqi; Lei, Dongying; Liu, Xinyi; Chen, Zipeng; Li, Jiaying; Huang, Liang; Liu, Huifen; Yang, Xuebin; Wei, Wei; Xie, Sijing (Frontiers in Bioengineering and Biotechnology, 2025)
IntroductionPeriodontal bone regeneration remains a significant challenge in clinical dentistry due to the complex structure of periodontal tissues and their limited intrinsic regenerative capacity. Innovative biomaterial-based strategies are therefore required. Polyphosphates (Poly(P)) have shown promising regenerative potential; however, conventional chemical synthesis methods are limited by high costs and product impurity concerns.MethodsWe established an eco-friendly biosynthetic strategy using a genetically engineered environmental bacterium overexpressing polyphosphate kinase (PPK1) to produce high-purity polyphosphates (Bio-Poly P) from wastewater-derived phosphate sources. Structural characterization was performed to confirm physicochemical properties. The effects of Bio-Poly P on human periodontal ligament stem cells (hPDLSCs) were assessed by CCK8 assays, qRT-PCR, alkaline phosphatase (ALP) activity, and Alizarin Red staining. In vivo osteogenic potential was evaluated using a murine periodontal bone defect model with micro-CT analysis after 4 weeks of implantation.ResultsIn vitro, Bio-Poly P at 1.25 and 2.5 mg/ml did not reduce hPDLSC proliferation at 24, 48, and 72 h, whereas higher concentrations (≥5 mg/ml) significantly inhibited proliferation (P < 0.0001). At day 7, Bio-Poly P at 0.25, 1.25, and 2.5 mg/ml significantly upregulated COL1A1 expression (P < 0.0001), while only 1.25 mg/ml enhanced OCN (P < 0.0001) and OPN (P < 0.01). No effect was observed on RUNX2 at this time point. By day 14, all three concentrations significantly increased the expression of RUNX2, OCN, OPN, and COL1A1. Enhanced ALP activity and calcium deposition were confirmed by biochemical assays and Alizarin Red staining, with the 1.25 mg/ml group showing the greatest mineralization. In vivo, Bio-Poly P significantly improved bone mineral density, bone volume/tissue volume ratio, and trabecular thickness compared with untreated defects, with regenerative outcomes comparable to the clinical control Bio-Oss® (P > 0.05).DiscussionThis study demonstrates that Bio-Poly P possesses favorable biosafety and osteoinductive properties, effectively enhancing osteogenic differentiation of hPDLSCs in vitro and promoting periodontal bone regeneration in vivo. By leveraging a cost-effective and sustainable biosynthetic production method, Bio-Poly P represents a promising alternative to chemically synthesized polyphosphates for clinical periodontal regeneration.